On the View of Another’s Discourse: incorporated genres in one of João Ribeiro’s chronicles - Campos, Maria Inês Batista (The ESPecialist, 2012)
This article is about one of João Ribeiro’s chronicles in the magazine Revista do Brasil, and discusses how an incorporated genre, such as a letter in French in this chronicle, is an important discourse procedure which shows the struggle of different voices. The theme of this chronicle is an incident that was erased from official Brazilian history. The author retells this incident from the point of view of a Brazilian voice in opposition to two others – Portuguese and French –, to discuss the different views concerning Brazilian identity at the beginning of the 20th century.